Histological and Immunohistochemical Characterization of Osteoimmunological Processes in Scaffold-Guided Bone Regeneration in an Ovine Large Segmental Defect Model - Finze, Ronja; Laubach, Markus; Serafini, Mairim Russo; Kneser, Ulrich; Savi, Flavia Medeiros (Biomedicines, 2023)
Large-volume bone defect regeneration is complex and demands time to complete. Several regeneration phases with unique characteristics, including immune responses, follow, overlap, and interdepend on each other and, if successful, lead to the regeneration of the organ bone's form and function. However, during traumatic, infectious, or neoplastic clinical cases, the intrinsic bone regeneration capacity may exceed, and surgical intervention is indicated. Scaffold-guided bone regeneration (SGBR) has recently shown efficacy in preclinical and clinical studies. To investigate different SGBR strategies over periods of up to three years, we have established a well-characterized ovine large segmental tibial bone defect model, for which we have developed and optimized immunohistochemistry (IHC) protocols. We present an overview of the immunohistochemical characterization of different experimental groups, in which all ovine segmental defects were treated with a bone grafting technique combined with an additively manufactured medical-grade polycaprolactone/tricalcium phosphate (mPCL-TCP) scaffold. The qualitative dataset was based on osteoimmunological findings gained from IHC analyses of over 350 sheep surgeries over the past two decades. Our systematic and standardized IHC protocols enabled us to gain further insight into the complex and long-drawn-out bone regeneration processes, which ultimately proved to be a critical element for successful translational research.